2022
DOI: 10.3389/fnbeh.2022.954382
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mediating effects of negative and positive religious coping between resilience and mental well-being

Abstract: Background:The purpose of the study was to examine more thoroughly the relationship between trait resilience and mental well-being. Although research demonstrates that this relationship is partially mediated by stress-related variables, no study has taken into account the mediating role of religious coping. We examined the mediating role of both variants of religious coping, positive and negative, along with specific strategies within the scope of religious coping strategies in a group of practicing Catholics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…However, it was identified that there is a relationship between stress, anxiety and depressive symptoms, [15] and it also highlights the weak negative association between negative coping and resilience. [23] In the present study, suicide attempt as an outcome and the other variables performing as predictors configured a higher sensitivity (96.8%) compared to the previous models. In this regard, a cohort study revealed that suicide attempt rates were three times higher in individuals with a previous ideation background or even attempts.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, it was identified that there is a relationship between stress, anxiety and depressive symptoms, [15] and it also highlights the weak negative association between negative coping and resilience. [23] In the present study, suicide attempt as an outcome and the other variables performing as predictors configured a higher sensitivity (96.8%) compared to the previous models. In this regard, a cohort study revealed that suicide attempt rates were three times higher in individuals with a previous ideation background or even attempts.…”
Section: Discussionmentioning
confidence: 49%
“…[22] The RCOPE scale has been used in researches about relationship between anxiety and depression symptons [15] and as mediating effect between resilience and well-being. [23] 2.3 Procedures 2.3.1 Data collection Initially, phone contacts and traveling to the intended locations were performed, aiming to reach potential participants; the instruments were self-applicable, lasting approximately 20 minutes. Invitations referring to the study were also released through electronic means/social networks, so that other individuals could learn about the research.…”
Section: Instrumentsmentioning
confidence: 99%